2021
DOI: 10.1042/bsr20210391
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the functions and prognostic values of synapse-associated proteins in lower-grade glioma

Abstract: Synapse and synapse associated proteins (SAPs) play critical roles in various neurodegeneration diseases and brain tumors. However, in lower-grade gliomas (LGG), SAPs have not been explored systematically. Herein, we are going to explore SAPs expression profile and its clinicopathological significance in LGG which can offer new insights to glioma therapy. In this study, we integrate a list of SAPs that covered 231 proteins with synaptogenesis activity and post synapse formation. The LGG RNA-seq data were downl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…It has been suggested that the tumor cells themselves are neurotoxic (through cytokine and neurotransmitter release) and can elicit seizures by disruption of neuronal pathways or through local glutamate concentration/metabolism changes. A decrease in glutamate uptake and an increase in its release by glioma cells and by neighboring nontumoral astrocytes and activated microglia lead to an excessive glutamatergic excitatory neurotransmission and to a higher risk of seizures [28,91,96,97]. Moreover, GABAergic signaling in the PTZ, affected by the extracellular glutamate, is also involved in both glioma growth and epilepsy [25,89,91,92,[97][98][99].…”
Section: Ptz and Epilepsy On Dlggmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the tumor cells themselves are neurotoxic (through cytokine and neurotransmitter release) and can elicit seizures by disruption of neuronal pathways or through local glutamate concentration/metabolism changes. A decrease in glutamate uptake and an increase in its release by glioma cells and by neighboring nontumoral astrocytes and activated microglia lead to an excessive glutamatergic excitatory neurotransmission and to a higher risk of seizures [28,91,96,97]. Moreover, GABAergic signaling in the PTZ, affected by the extracellular glutamate, is also involved in both glioma growth and epilepsy [25,89,91,92,[97][98][99].…”
Section: Ptz and Epilepsy On Dlggmentioning
confidence: 99%
“…Moreover, GABAergic signaling in the PTZ, affected by the extracellular glutamate, is also involved in both glioma growth and epilepsy [25,89,91,92,[97][98][99]. Additionally, alkalization of the peritumoral neocortex [87], synapse-associated proteins [28], and activation of the mammalian target of rapamycin (mTOR) pathway [25] have been implicated in epileptogenesis. Dey et al (2021) demonstrated increased spontaneous glutamatergic and GABAergic synaptic activity onto pyramidal neurons in the peritumoral samples of DLGG in patients with a history of seizures as compared with those in patients without seizures [27].…”
Section: Ptz and Epilepsy On Dlggmentioning
confidence: 99%
See 1 more Smart Citation
“…LGGs are some of the most common tumors in the central nervous system. However, the heterogeneity and complexity of these tumors have delayed the development of specific and effective predictive biomarkers for LGGs ( 21 , 22 ). An effective prognostic model based on specific biomarkers could accurately forecast survival outcomes, allowing efficient management of patients with LGGs.…”
Section: Discussionmentioning
confidence: 99%
“…The CNS is also rich in neurotransmitters, which create a unique microenvironment for brain tumors, where neurotransmitter-mediated intracellular signaling pathways can be transduced by cancer cells and induce cancer cell growth, activation, and metastasis ( 7 ). With the progressive discovery of glioma synapses and metastatic neuronal synapses, it is believed that neurotransmitters may play crucial roles in tumor growth, and the speculation that tumor cells may stimulate their innervation has been confirmed ( 8 , 9 ). It has been suggested that microenvironment interaction, especially the abnormal interaction between glial cells and synapses, is one of the neuropathological mechanisms underlying Rett syndrome, Down syndrome, spinal muscular atrophy, and other diseases ( 10 ).…”
Section: Introductionmentioning
confidence: 99%